Tax Planning and Avoidance on Firm Value - Vista Yulianti; Jamian Purba; Widya April Ningrum (East Asian Journal of Multidisciplinary Research, 2023)
The practice of collecting taxes on companies is one of the burdens that will reduce the company's profits. While the company expects to achieve maximum profits, high profits will make the company's value high, as a result of which it can prosper its shareholders. The company therefore minimizes tax payments through planning and tax avoidance. This study aims to test the effect of tax planning and tax avoidance on firm value in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange in the 2019–2021 period. This study used secondary data. Measuring the value of the firm using PBV (price to book value), which is the market price per share divided by the book value of the shares, The sampling technique used is purposive sampling. Of the 26 manufacturing companies in the food and beverage subsector, only 17 met the sample criteria for this study. The analysis method used is multiple linear regression. By using regression analysis, it can be partially known that tax planning affects the value of the company. Meanwhile, tax avoidance does not affect the value of the company. Simultaneously, it can be seen that tax planning and tax avoidance do not affect the value of the company.